Design & investigation of 10x10 gbit/s MDM over hybrid FSO link under different weather conditions and fiber to the home - Alaan Ghazi; S. A. Aljunid; Awab Noori; Syed Zulkarnain Syed Idrus; C. B. M. Rashidi; Aras Al-Dawoodi (Institute of Advanced Engineering and Science, 2019)
In this paper, we design and investigate 10-channels of mode division multiplexer (MDM) over hybrid free-space optics (FSO) link in several weather conditions to achieve the maximum possible medium range and fiber to the home (FTTH) for high bandwidth access networks. System capacity can be effectively increased with the use of MDM over hybrid FSO-FTTH. In this study, a 10-channel MDM over FSO-FTTH system has been analyzed in different weather conditions that operate at 1550 nm wavelength. The simulated system has transmitted 100 Gbit/s up for a distance of 3200 meters FSO in superbly clear weather condition. It also transmitted 100 Gbit/s up for a distance of 650 meters FSO during heavy rain. The validation of this study is measures based on eye diagrams bit-error rates (BER) that have been analyzed.